The Influence Of Service Quality And Facilities On Interest In Revisiting At Grand Arkenso Parkview Semarang Hotel - Widya Paramitha Sari Sijabat; Julian Andriani (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study takes the title Effect of Service Quality and Facilities on Interest in Visiting Again at Grand Arkenso Parkview Semarang Hotel. The purpose of this study was to analyze the effect of service quality and facilities on interest in visiting again. This study uses a survey design, which is a study that takes samples from a population using a questionnaire as a data collection tool. The samples us was 96 respondents Grand Arkenso Parkview Semarang Hotel. Data analyze in this study uses multiple linear regression methods. The results of this study are the quality od service (X1) has a positive and significant effect on interest in visiting again, facility (X2) has a positive and significant effect on interest in visiting again. Based on the F test, it shows that the quality of service and facilities has a simultaneous and significant effect on interest in visiting again at Grand Arkenso Parkview Semarang Hotel. Based on multiple regression test, from the two regression coefficient values of the independent variables (service quality and facilities) that most influence on the dependent variable (interest in visiting again) is the service quality that is equal to 0.440.